Are we under Siege? US Popular Perceptions of Japan and China in the Post-Cold War Era - Ranger Stephen (Centre for East and South-East Asian Studies, 2025)
With the end of the Cold War, the early 1990s witnessed a peak in Japan-bashing within popular discourse in the United States. Such sentiments though declined as Japan’s economy weakened from the mid-1990s and were replaced by new fears of China following the Taiwan Strait Crisis 1995/6. This article seeks to trace and contrast the perceptions of Japan and China during the 1990s as represented in the techno-thriller genre of popular US literature. The findings will show that Japan was treated as more of an existential threat to America than China due to historical factors and the strong economic presence in the US. This has relevance for interpreting how China will be perceived in the 2020s as its economy becomes more prominent in the US.